2015
DOI: 10.1002/anie.201500628
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Activated Molecular Switches

Abstract: The ability to influence key properties of molecular systems by using light holds much promise for the fields of materials science and life sciences. The cornerstone of such systems is molecules that are able to reversibly photoisomerize between two states, commonly referred to as photoswitches. One serious restriction to the development of functional photodynamic systems is the necessity to trigger switching in at least one direction by UV light, which is often damaging and penetrates only partially through m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
646
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 695 publications
(657 citation statements)
references
References 95 publications
(232 reference statements)
5
646
0
6
Order By: Relevance
“…611 In photoactive materials light absorbed by chromophores can be converted into directed functionality, typically by means of photoinduced isomerization of nitrogen or carbon containing double bonds and pericylic reactions. 1227 Indeed, E – Z isomerization results in large amplitude changes in structure as well as chemical and physical properties. 2832 …”
Section: Introductionmentioning
confidence: 99%
“…611 In photoactive materials light absorbed by chromophores can be converted into directed functionality, typically by means of photoinduced isomerization of nitrogen or carbon containing double bonds and pericylic reactions. 1227 Indeed, E – Z isomerization results in large amplitude changes in structure as well as chemical and physical properties. 2832 …”
Section: Introductionmentioning
confidence: 99%
“…[4] The light response of certain materials is associated to the presence of light active groups such as azobenzene that isomerizes under illumination.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that for specific linear azo polymers, this color can be removed, leading to permanent topographies [51]. Extensive research towards new applicable light triggered molecules [113] can lead to a more natural approach where the sun can be used as the light source [114]. The use of visible light triggering molecules (including azobenzenes) will continue to result in colored coatings.…”
Section: Discussionmentioning
confidence: 99%